Analisis Pengaruh Beban Dan Dimensi Berlebih Kendaraan Angkutan Barang Terhadap Ketahanan Sasis Dan Sistem Suspensi Kendaraan - Fahmadi, Aat Eska; Rafinanda, Rahma; Aziz Kurniawan, Moch; Sugianto, Sugianto; Arief Novianto, R. (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
The widespread use of overloaded and overdimensioned freight vehicles (ODOL) has become a serious issue, affecting not only road infrastructure but also the technical components of vehicles, such as the chassis and suspension systems. This study aims to directly analyze the impact of excessive load and dimensions on the durability of the chassis and leaf springs as part of the vehicle’s suspension system. The main problem examined is the extent to which ODOL conditions contribute to technical damage in the chassis and leaf springs.This research adopts an experimental approach by collecting data through field observations, driver interviews, and static load simulations using the Finite Element Analysis method with SolidWorks software. Simulations were conducted on the chassis and leaf springs of an open-bed truck with a 1.2 axle configuration, using three load variations (10%, 20%, and 30% over the vehicle's Gross Vehicle Weight Rating or GVWR). The simulations also aimed to identify the point at which the chassis and leaf springs experience material failure or fracture. The results show a significant increase in stress and displacement in both the chassis and leaf springs under 10%, 20%, and 30% overload conditions. Furthermore, the factor of safety values indicate a declining level of material safety as the load increases. Material failure in the chassis occurred at 55% overload, while the leaf springs failed at 150.7% overload. Based on observations, interviews, and simulation results, this study reinforces the importance of enforcing regulations on vehicle weight and dimensions. In addition to damaging infrastructure, ODOL vehicles significantly compromise the structural integrity of the chassis and suspension system, leading to increased vehicle maintenance costs. This research is expected to serve as a technical reference for business operators and policymakers in supporting the Zero ODOL program and as a basis for developing more evidence-based road safety policies.